Development of flesh flies (Diptera: Sarcophagidae) of medico-legal importance on pig carcass in the Cerrado of Brazil - Silva, José Orlando de Almeida; Brasil, Leandro Schlemmer; Silva, Eduardo Almeida; Neves, Liliane Torres; Carvalho-Filho, Fernando da Silva (Revista Brasileira de Criminalística, 2023)
With the aim of contributing data on flies (Diptera) to assist in forensic processes in the medical-legal area, this study investigated species of flesh flies (Diptera: Sarcophagidae) that develop in pig carcass and at what stages of decomposition they disperse from the carcass in the Cerrado of the Northeast region of Brazil. Larvae and pupae were collected daily using sawdust trays placed beneath cages containing pig carcass. The material collected was allowed to complete development to adults in the laboratory under natural conditions of temperature and relative humidity. Adult male specimens were subsequently identified. The experiments were conducted in July and August 2010, in the dry season. A total of 140 adult specimens belonging to five species were obtained. The most abundant species were Peckia (Squamatodes) trivittata (Curran, 1927) (n = 109) and Peckia (Squamatodes) ingens (Walker, 1849) (n = 28), that dispersed from the carcasses during the dark putrefaction (or coliquative stage) and butyric fermentation stages. Helicobia neuzalmeidae Silva, Brasil, De-Souza & Carvalho-Filho, 2022, and Oxysarcodexia timida (Aldrich, 1916) left carcasses at the dark putrefaction stage as well. Peckia (Euboettcheria) collusor (Curran & Walley, 1934) was obtained during the dry stage only. For the first time, Oxysarcodexia timida was observed developing in a pig carcass. The immatures of P. (S.) trivittata and P. (S.) ingens can aid in determining the time of death of corpses discovered in Brazil's Northeastern Cerrado.